2018
DOI: 10.1111/jcpt.12678
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and allele frequencies of TYMS rs2790 A > G polymorphism in a Chinese paediatric population with acute lymphoblastic leukaemia

Abstract: The results of this study confirmed the significant ethnic differences in the distributions of the TYMS rs2790 A > G polymorphism. Whereas there was evidence of differences in MTX blood levels according to genotype, our study was not powered to show whether this would lead to more haematological toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…Critically, an understanding of how elevated levels of TS promote carcinogenic events could also help to explain why TS 3 -UTR polymorphisms may affect CRC occurrence and prognosis. According to a recent report, compared with the rs2790 AA genotype at the 3 -UTR of TS, the rs2790 GG genotype was associated with a significantly higher risk of acute lymphoblastic leukaemia (ALL) [37]. The present study confirmed that the presence of the TS 3 UTR polymorphism (rs151264360) increased the risk of persistence of cervical cancer [38].…”
Section: Discussionsupporting
confidence: 83%
“…Critically, an understanding of how elevated levels of TS promote carcinogenic events could also help to explain why TS 3 -UTR polymorphisms may affect CRC occurrence and prognosis. According to a recent report, compared with the rs2790 AA genotype at the 3 -UTR of TS, the rs2790 GG genotype was associated with a significantly higher risk of acute lymphoblastic leukaemia (ALL) [37]. The present study confirmed that the presence of the TS 3 UTR polymorphism (rs151264360) increased the risk of persistence of cervical cancer [38].…”
Section: Discussionsupporting
confidence: 83%
“…The combination of increased TYMS expression (tandem repeat x3) and reduced function of MTHFR (homozygous for the 677T allele) was associated with increased risk of MTX-induced hematologic toxicity but not plasma MTX concentrations [ 71 ]. Only two out of 14 studies found an association between SNPs in TYMS and MTX elimination [ 42 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…[14] Previous clinical studies have shown that TYMS polymorphisms are associated with various of cancers, such as gastric cancer, [14] lung cancer, [17] hepatocellular carcinoma, [18] and acute lymphoblastic leukemia. [19] Additionally, TYMS polymorphisms may predict the chemosensitivity to 5-fluorouracil, doxorubicin, cyclophosphamide, pemetrexed and so on. [20,21,9] TYMS SNPs influence cancer susceptibility and chemosensitivity via effects on TYMS expression [22] and its effects differ with respect to race.…”
Section: Discussionmentioning
confidence: 99%
“…Rs2790 is in linkage disequilibrium with a functional SNP (TSER, three or two repeats of a 28-bp sequence) in TYMS [14]and modulates TYMS expression by its effects on the binding of hsa-miR-1248 to its target gene. [19] However, little is known about the functionality of these two SNPs. More experimental studies are urgently needed to clarify the mechanism underlying the effects of TYMS polymorphisms.…”
Section: Discussionmentioning
confidence: 99%